Building a credible and believable narrative: the role of direct examination in expert witness testimony - Noraini Ibrahim, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2007)
Educational best practices deem that students must be able to access, utilize and produce the discourse of the target community - a site that is shaped by social, institutional and historical underpinnings. The domain of law in Malaysia and the Malaysian courtroom, for instance, is one site that is influenced and shaped by such variables. To participate meaningfully in such a domain thus requires participants to be aware of literacy practices, which in turn, involve the acquisition and learning of the relevant and existing complex roles, identities, codes, registers and social artifacts. While officers of the court (judges and counsels for instance), are trained participants, witnesses who are called to court to give evidence are not. As such during direct examinations, which mark the start of the process of evidence taking, witnesses are usually led by counsels through the questioning process to build a foundation of their narrative. This paper, which is based on a case study of criminal trial in Malaysia, will show how the successful undertaking of direct examinations, is crucial for a narrative version that is believable and credible. The roles of the judge, counsels and expert witnesses in the adversarial system practiced in Malaysia and the strategies employed by the counsels during the direct examinations of expert witnesses will also be highlighted.